Oribatid mites (Acarina, Oribatida) from French Guyana: review of the genus Rhynchoribates and description of three new specie - Miko, Ladislav (Zootaxa, 2016)
One new genus (Eurhynchoribates n. gen.) and three new subgenera (Rhynchoribatodes n. subgen., Parhynchoribates n. subgen. and Tectorhynchoribates n. subgen.) are proposed on the basis of review of known species of genus Rhynchoribates Grandjean, 1929 and on the basis of description of three new species—Rhynchoribates (s. str.) danbartai n. sp., Rhynchoribates (Tectorhynchoribates) jurobales n. sp. and Rhynchoribates (Rhynchoribatodes) dynastes n. sp.—from the territory of French Guyana. All known species of Rhynchoribates are discussed and their position into newly defined genera and subgenera proposed. Detailed differential diagnoses are given for all new taxons.